The role of insects as sustainable resources in food and tourism: A comparative global-local analysis - Mahadimenakbar Mohamed Dawood; Fiffy Hanisdah Saikim (Universiti Malaysia Sabah, 2025)
This paper highlights insects as natural resources for food and attractions in the nature tourism industry. We analyse the subjects from a global perspective and compare them locally. Edible insects have been proposed as a more environmentally sustainable and nutritious alternative to conventional livestock. The identification of over 2000 edible insect species has firmly entrenched entomophagy as a widely accepted practice across various regions in Africa, America, and Asia. With the burgeoning global population and diminishing agricultural land, the current practice of relying on domesticated animal protein is incontrovertibly unsustainable. Insects, on the other hand, unequivocally emerge as a viable solution. Their ability to be raised in large numbers in a smaller area, rapid growth, and minimal resource requirements firmly establish them as a sustainable source of nutrition. In addition to their role as a sustainable food source, certain insects, notably fireflies and butterflies, unequivocally contribute to the nature tourism industry by attractively drawing in tourists and substantially benefiting local populations. The potential for economic growth and development in the tourism industry is significant. Entomotourism, particularly in Sabah, Malaysia, is incontrovertibly gaining momentum, with firefly-watching activities notably propelling significant revenue generation. Undeniably, the significance of insects as both a fundamental component of food security and as alluring attractions in the nature tourism industry cannot be overstated.